Relationship network, knowledge transfer and open innovation behavior of SMEs from China - Menglin Ni; Muwen Wang (PLoS ONE, 2025)
In the context of globalization and digital transformation, small and medium-sized enterprises (SMEs) face increasing resource constraints that limit traditional innovation models. This study investigates how Chinese SMEs’ relational networks influence their open innovation behaviors, examining the mediating role of knowledge transfer and the moderating effect of innovation strategic orientation. Through questionnaire data collected from 329 SMEs’ middle and senior managers, we find that: (1) Firm relational networks significantly enhance knowledge transfer; (2) Innovation strategic orientation positively moderates the relationship between networks and knowledge transfer; and (3) Both networks and knowledge transfer exhibit strong positive impacts on SMEs’ open innovation behaviors, with knowledge transfer acting as a partial mediator. The research reveals the mechanism through which relational networks drive open innovation via knowledge mobilization while highlighting the critical regulatory role of strategic innovation focus. These findings contribute to understanding open innovation dynamics in emerging markets by demonstrating the sequential pathway: network development → knowledge acquisition → innovation outcomes. For practitioners, the study underscores the strategic value of cultivating robust relational networks aligned with innovation objectives, enhancing internal knowledge circulation capabilities, and maintaining adaptive strategic orientations to capitalize on external opportunities. The research provides theoretical and practical guidance for SMEs seeking sustainable competitive advantages through open innovation strategies in knowledge-based economies.